2022
DOI: 10.1523/eneuro.0106-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Hyperalgesia and Somatic Signs of Heroin Withdrawal in Male and Female Mice

Abstract: Opioid withdrawal involves the manifestation of motivational and somatic symptoms. However, the brain structures that are involved in the expression of different opioid withdrawal signs remain unclear. We induced opioid dependence by repeatedly injecting escalating heroin doses in male and female C57BL/6J mice. We assessed hyperalgesia during spontaneous heroin withdrawal and somatic signs of withdrawal that was precipitated by the preferential μ-opioid receptor antagonist naloxone. Heroin-treated mice exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Additionally, increased anxiety-like behavior was found one week into abstinence from fentanyl. Withdrawal from opioids such as heroin and morphine has been shown to result in hyperalgesia in humans (74,75) and similarly in rats and mice (16,18). Recent studies have shown oxycodone withdrawal to result in increase of mechanical pain sensitivity in rats (10) and somatic withdrawal signs in mice (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, increased anxiety-like behavior was found one week into abstinence from fentanyl. Withdrawal from opioids such as heroin and morphine has been shown to result in hyperalgesia in humans (74,75) and similarly in rats and mice (16,18). Recent studies have shown oxycodone withdrawal to result in increase of mechanical pain sensitivity in rats (10) and somatic withdrawal signs in mice (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…In those rodent models, there is a clear pattern of increasing drug intake over time, accompanied by intensified drug-seeking behavior. Withdrawal symptoms are also a hallmark of drug dependence and upon withdrawal from opioids, both rats and mice exhibit allodynia (1518), along with anxiety-like behaviors (19), and a spectrum of other withdrawal-related physical symptoms (2023). These observations highlight the translational validity and value of such models in deepening our comprehension of the behavioral and physiological changes associated with OUD.…”
Section: Introductionmentioning
confidence: 99%
“…Heightened mechanical sensitivity was associated with higher opioid preference in mice with a history of stress but not in controls [ 67 ]. Naloxone-precipitated withdrawal in the LgA group loaded on a third independent factor, suggesting different brain circuitries compared with hyperalgesia in LgA mice [ 68 ]. These findings highlight qualitative differences between behavioral phenotypes of mice with different levels of drug access.…”
Section: Discussionmentioning
confidence: 99%
“…The c-fos is an excellent biomarker for identifying synaptic activation ( Torres-Hernandez et al, 2016 ), and the relative expression of c-fos was more than twice as high in zebrafish exposed to high fentanyl as it was in the control group. Experiments on mice revealed a correlation between c-fos expression in a specific subset of brain areas and opioid hyperalgesia and physical withdrawal symptoms ( Alvarez-Bagnarol et al, 2022 ). In addition, the expression level of c-fos mRNA in the zebrafish brain increased considerably following nicotine abstinence in the zebrafish nicotine withdrawal experiment ( Ponzoni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%